FOOD HABITS AND DIET OVERLAP OF TWO SYMPATRIC CARNIVORE SPECIES IN CHITRAL, PAKISTAN - S. Shabbir; M. Anwar; I. Hussain; M. A. Nawaz (Journal of Animal and Plant Sciences, 2013)
Two carnivore species i.e. Grey wolf (Canis lupus) and Asiatic jackal (Canis aureus) spread over wide range of habitats in Pakistan, showing sympatric distribution in many areas including Chitral area of Hindu Kush Range. The present study determined the food habits and diet overlap of these two species in Chitral, Pakistan. Fifty scat samples, 25 each of wolf and jackal, were collected and analyzed to determine their diet composition. Hair characteristics such as medullae and scale patterns were used to identify the mammalian preys consumed by these predators. Wolf consumed 14 prey species while jackal consumed 13, among which 11 species were common in their diets. Domestic sheep, Palm civet and Golden marmot dominated the diet of wolf while Palm civet, Golden marmot, Cape hare and Wood mouse were main prey species found in the scats of jackal. Diet overlap factor indicated a high prey overlap between the two species, providing chances of competition. The potential habitats along with their natural prey species need to be protected for the conservation of these two species, especially the Endangered one, the Grey wolf. Compensation to the owners of livestock killed by wolf could help in saving this species from retaliating killing.
Keywords: Grey wolf; Asiatic jackal; Diet composition; Diet overlap; Conservation; Chitral Pakistan